Prior learning in accounting and its impact on student performance in first courses in accounting: Addressing the gaps in the literature - Perrin, Brian; Robinson, P. (2016)
The changed and more diversified profile of university students enrolling in accounting first courses (and beyond) has accentuated the need for accounting academics to be fully aware of those factors having a significant influence on student performance. Over the past 30 years a well-established research literature has emerged that has sought to identify and measure the significance of factors believed to have an impact on student performance. Unfortunately, the identification of those factors having a significant impact on student performance in university accounting courses is still far from settled. This study posits that the contrary results reported in prior research may be attributable to differences in how key independent variables have been defined and measured. In this study, we use a tighter specification of independent and dependent variables and find that academic preparedness (as measured by tertiary entrance rank scores) and prior learning in accounting are both highly significant factors in explaining student performance in a Western Australian university’s first course in accounting. Moreover, after controlling for the impact of academic preparedness, for students possessing prior learning in accounting, they achieve a significant lift in performance in the first course in accounting than conferred by their tertiary entrance score. The policy implication of this result is that Australian universities, perhaps unintentionally, privilege the learning and academic performance in first courses in accounting of those students who already possess prior learning in accounting.